The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00256-018-3097-z
|View full text |Cite
|
Sign up to set email alerts
|

Single-shot CT after wrist trauma: impact on detection accuracy and treatment of fractures

Abstract: Objective To evaluate accuracy of fracture detection and therapeutic impact of a single-shot CT protocol as a primary imaging tool in all patients with clinical suspicion of wrist injury, and evaluate the resulting impact on therapy. Materials and methods We performed a single-institution study on all patients with suspicion of fractures of the wrist and carpus. All patients underwent conventional radiography, thereafter single-shot wrist CT, and then 1-year follow-up. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…ULD-CT significantly increased the overall fracture detection rate-in 36 extremities (36/207; 17.4%) a fracture was detected with ULD-CT where DR failed to detect a fracture. The diagnostic findings are concordant with a previous study comparing the accuracy of fracture detection between a low-dose CT protocol and conventional radiography for wrist trauma [12]. However, our study has further evaluated the diagnostic performance of a low-dose CT protocol to also include ankle and midfoot trauma, as well as workflow parameters.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…ULD-CT significantly increased the overall fracture detection rate-in 36 extremities (36/207; 17.4%) a fracture was detected with ULD-CT where DR failed to detect a fracture. The diagnostic findings are concordant with a previous study comparing the accuracy of fracture detection between a low-dose CT protocol and conventional radiography for wrist trauma [12]. However, our study has further evaluated the diagnostic performance of a low-dose CT protocol to also include ankle and midfoot trauma, as well as workflow parameters.…”
Section: Discussionsupporting
confidence: 87%
“…Clinical studies have shown that implementation of ASIR-V can decrease the mean RD between 34 and 35% while maintaining image quality [13,14]. Previously reported mean RD for low-dose CT evaluation of fractures of the peripheral skeleton has been in the range of 10-800 μSv [12,[15][16][17][18] and for cone-beam CT (CBCT) in the range of 0.9-14.3 μSv [19]. Our ULD-CT protocol has, to our knowledge, the lowest reported mean RD (0.59 μSv) for the peripheral skeleton in the literature, corresponding to around 1.7 h of exposure to background radiation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Physicians should be aware that tenderness in the anatomical snuff box (ASB), tenderness over the scaphoid tubercle and pain on longitudinal compression of the thumb have limited added value in a diagnostic process for a scaphoid fracture. The present systematic review identified eight supplementary imaging studies [58,61,65,66,[68][69][70]74], subdivided into MRI [66], CT [58,66,[68][69][70], BS [66] and US [61,65,74]. The overall conclusion is that imaging tests were found to be moderately accurate for a definitive diagnosis.…”
Section: Discussionmentioning
confidence: 91%
“…To our knowledge, all first authors of those five studies were working in a hospital care setting, so we assume all to have been done in hospital care. History taking, physical examination and imaging as index tests were nvestigated in 0%, 20% (7/35) [43, 44, 46, 47, 67 71, 74] and 86% (30/35) [75][76][77] of the studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In 13 of the 35 studies [43,44,51,53,56,57,59,61,62,70,71,73,74], patient selection was not well documented. Furthermore, the risk of bias was predominantly due to the absence of a proper description of the index test (9/35) [43,47,49,51,55,57,61,65,71] or the reference standard (13/35) [43,46,49,51,52,55,57,65,67,69,72,74,75]. Twelve of the studies (34%) demonstrated no limitations when risk of bias was assessed, according to QUADAS-2 [45,48,50,54,58,60,63,64,66,68,76,77].…”
Section: Quality Assessmentmentioning
confidence: 99%